SOCIAL NETWORK STRUCTURE AND FIRMS’ INTERNATIONALIZATION: NEW INSIGHTS FROM A WHOLE-NETWORK PERSPECTIVE - Renan Oliveira; Björn Jindra; Ariane Roder Figueira (Internext: Revista Eletrônica de Negócios Internacionais, 2024)
Objective: The aim of this study was to analyze the social network structure of the oil and gas (O&G) cluster in Rio de Janeiro, Brazil. We explore whether internationalized firms concentrate in specific sections of the social network, and scrutinize whether internationalization is associated with a firm’s attributes and its direct and indirect network ties. Method: This research applies social network analysis, which allows us to identify dense sections, popular nodes, and strategic position. We apply partitioning techniques to determine the extent to which a firm’s internationalization is affected by those to whom it is connected. Main results: Our findings show that internationalized firms concentrate in dense sections of the network, which are characterized by high interconnectedness. Furthermore, there is indicative evidence that interaction among firms and their attributes embedded in the social network structure is associated, at least in part, with the diffusion of internationalization. Relevance / Originality: Most studies targeting the network focus on the so-called ego network. This study applies a whole-network perspective to consider popular communities and central nodes and, ultimately, show how social behavior is diffused within the social network structure. Theoretical / Methodological Contributions: Drawing upon the network theory, we emphasize interdisciplinarity to advance international business (IB) scholarship. In particular, we qualify the Uppsala model’s assumption of network/relational capability, that is, the ability to build, sustain, and coordinate relationships by demonstrating the relevance of the social network structure to the internationalization process.